2021
DOI: 10.1083/jcb.202109111
|View full text |Cite
|
Sign up to set email alerts
|

Engineered synaptic tools reveal localized cAMP signaling in synapse assembly

Abstract: The physiological mechanisms driving synapse formation are elusive. Although numerous signals are known to regulate synapses, it remains unclear which signaling mechanisms organize initial synapse assembly. Here, we describe new tools, referred to as “SynTAMs” for synaptic targeting molecules, that enable localized perturbations of cAMP signaling in developing postsynaptic specializations. We show that locally restricted suppression of postsynaptic cAMP levels or of cAMP-dependent protein-kinase activity sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…An important question that remains largely unanswered is how latrophilins function on a molecular level to promote excitatory and inhibitory synapse formation. Recent findings suggest G-protein binding of Latrophilin-3 and localized synaptic cAMP signaling to be essential molecular events for excitatory synapse formation ( Sando et al, 2021 , 2022 ; Wang et al, 2024 ). Neuronal isoforms of Latrophilin-1 bind to multiple G-proteins with a preference for Gs ( Wang et al, 2024 ), which could mean that the inhibitory synapses formed by Lphn1 depend on localized Gs-cAMP signaling cascades but might also include other G-proteins.…”
Section: Discussionmentioning
confidence: 99%
“…An important question that remains largely unanswered is how latrophilins function on a molecular level to promote excitatory and inhibitory synapse formation. Recent findings suggest G-protein binding of Latrophilin-3 and localized synaptic cAMP signaling to be essential molecular events for excitatory synapse formation ( Sando et al, 2021 , 2022 ; Wang et al, 2024 ). Neuronal isoforms of Latrophilin-1 bind to multiple G-proteins with a preference for Gs ( Wang et al, 2024 ), which could mean that the inhibitory synapses formed by Lphn1 depend on localized Gs-cAMP signaling cascades but might also include other G-proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the WRC regulatory pathway appears to integrate cues from other signaling pathways encompassing PKA 62 , 63 , 111 . Moreover, a subset of protein kinase pathways, including PKA and postsynaptic cAMP signaling, is essential for compartmentalized signaling at excitatory synapses 112 114 , suggesting the fascinating hypothesis that differentially activated WRC pathways determine the strength of intracellular signals in postsynaptic neurons (Fig. 2 ).…”
Section: Synaptic Functions Of the Wrcmentioning
confidence: 99%
“…[78] A follow-up study showed that Lphn2 and Lphn3 act as constitutive GPCRs and upregulate cyclic adenosine monophosphate (cAMP) levels via binding to G-proteins and arrestins, [30] which is consistent with the idea that compartmentalized intracellular calcium transient levels could dictate synaptic specificity. [14,69] Systematic studies are needed to assess whether the identified functions and mechanisms of Lphns in the hippocampal neural circuits are canonical, given that Lphn2 and Lphn3 appear to have different actions in the cerebellum. [80] Moreover, it is unclear how teneurins and/or FLRTs distinctively cooperate with Lphn2 and Lphn3 to mediate synaptic specificity.…”
Section: Lphn2 and Lphn3 Direct Synapse Specificity By Forming Synapt...mentioning
confidence: 99%
“…Excitatory synaptic response & feedforward inhibition (DG → CA3 circuit) [99] LRRTM3 AMPAR-and NMDAR-mediated response (MEC → DG circuit) [88 ] MDGA1 Negative regulation of inhibitory synaptic strength & GABA release (SST + IN → CA1 PN circuit) [62] AMPAR, α-amino-3-hydroxy- showed that compartmentalized postsynaptic signaling is involved in synapse assembly, [14] it remains unclear how the various trans-synaptic signaling pathways contribute to shaping specific properties of neural circuits.…”
Section: Synaptic Cam Synaptic Function Referencesmentioning
confidence: 99%
See 1 more Smart Citation